An alternative technique to reduce time, cost and human effort during natural or manufactured disasters - Al-Janabi, Samaher; Alkaim, Ayad; Rahem, Ahmed (Institute of Advanced Engineering and Science, 2022)
The world suffers from a very large number of missing persons, ranging from about 250,000 to about one million people for various reasons in recent years. Therefore, the process of finding and tracing the missing persons as a result of a plane crash, fire or explosion in a particular area is a humanitarian and religious and national duty, and is one of the most important issues in our country. So, the idea of using a drone to find missing people was invested. We have designed system that collects real-time data and analyzes in a smart way and utilizes global positioning system (GPS) to locate people and track their impact. The idea of this work has been developed and implemented. They represent it in the form of a triangular problem, which included: First, how to locate the missing persons and send video broadcasts to a calculator or mobile device remotely. Analyze the data collected in real time, and send a report identifying the safe path that can be taken to reach the missing persons. The second stage is collection the data in the master computer and analysis it, while the final stage determines the coordinates of the location to the missing persons and the best possible way to reach of them.